2022
DOI: 10.2147/idr.s359833
|View full text |Cite
|
Sign up to set email alerts
|

The Threat of Carbapenem-Resistant Gram-Negative Bacteria in Patients with Hematological Malignancies: Unignorable Respiratory Non-Fermentative Bacteria-Derived Bloodstream Infections

Abstract: Background Carbapenem-resistant Gram-negative bacteria (CRGNB) bloodstream infection (BSI) pose a significant threat to the prognosis of hematologic malignancies (HM) patients. Understanding the distribution of pathogenic bacteria, changes in carbapenem-resistant trends, risk factors for CRGNB infections, and exploring the early detection measures can help reduce mortality. Methods We conducted a multicenter retrospective study of Gram-negative bacteria (GNB) BSI in pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“… 37 It was deduced that our result of irrelevance between sources of infection and in-hospital mortality was more convincing for precluding selection bias, as the aforementioned prospective study was limited to carbapenem-resistant Klebsiella pneumoniae , the most frequent but hard to treat causative pathogen in hospital-acquired pneumonia. However, it should be noted that multi-drug resistant bacteria has been linked to poor outcomes of patients with HM, especially carbapenem-resistant Gram negative bacteria, 38 , 39 despite that our study failed to record the antimicrobial susceptibility phenotypes of bacteria strains due to the limited resources.…”
Section: Discussionmentioning
confidence: 90%
“… 37 It was deduced that our result of irrelevance between sources of infection and in-hospital mortality was more convincing for precluding selection bias, as the aforementioned prospective study was limited to carbapenem-resistant Klebsiella pneumoniae , the most frequent but hard to treat causative pathogen in hospital-acquired pneumonia. However, it should be noted that multi-drug resistant bacteria has been linked to poor outcomes of patients with HM, especially carbapenem-resistant Gram negative bacteria, 38 , 39 despite that our study failed to record the antimicrobial susceptibility phenotypes of bacteria strains due to the limited resources.…”
Section: Discussionmentioning
confidence: 90%
“…This was not very prevalent in our study, since only 40% of the studied population had recent exposure to carbapenems. Carbapenem resistance has dramatically increased in hemato-oncology patients with gram negative bacilli BSI in recent years and is associated with a worse outcome, especially for non-fermenting bacteria including Acinetobacter and Stenotrophomonas [ 35 ]. In a real-world, multicenter, retrospective case-control study from five centers in the southeast United States assessing 325 patients, S. maltophilia non-susceptibility had a prevalence of ∼50% to at least one first-line or commonly used agent [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, analysis of co-infections showed that 50%–85% of patients with carbapenem-resistant gram-negative bacilli bloodstream infections (BSI) had also pulmonary infections. Sputum culture results suggested that sputum culture positivity rate was as high as 57.1%–66.7% in patients with carbapenem-resistant A.baumannii and S. maltophilia BSI [ 35 ]. The latter underlies the need for infections control bundle implementation against HAP/VAP [ 38 ], but also the need for early screening of the respiratory tract specimens, in order to timely detect multidrug-resistant pathogen colonization and protect patients from breakthrough BSI.…”
Section: Discussionmentioning
confidence: 99%
“…In patients receiving chemotherapy for haematological malignancy, S. maltophilia along with A. baumannii contributed independently towards the 30-day mortality during BSIs, surpassing common pathogens, such as Enterobacterales [63]. Moreover, in a retrospective Chinese study of BSIs in patients with hematologic malignancies, the early (7-day) mortality of NFGNB was higher than Enterobacterales (22.6% vs. 9.7%, P < 0.001, respectively), while another Chinese study on BSIs by carbapenem-resistant Gram-negative bacteria, also in patients with hematologic malignancy, had similar results regarding early mortality [64,65]. Finally, another NFGNB associated with infections and increased mortality in haematological malignancies is B. cepacia, with the respiratory tract as the most frequent site of infection [66 ▪ ].…”
Section: Infections In Immunocompromised Hostmentioning
confidence: 94%